The Influence Of Brand Image, Product Quality And Lifestyle On The Decision To Purchase An Iphone Smartphone In Surabaya - Ramadhan, Muhammad Rizky Awwalul; Aminah, Siti; Hariyana, Nanik (UNIVERSITAS PAKUAN, 2024)
The increasingly rapid development of technology has made people's daily activities easier, so that dependence on technology, especially smartphones, is increasing. The purpose of this study is to examine how factors like lifestyle, product quality, and brand perception affect people's decisions to buy iPhones. Participants were iPhone-using students from UPN Veteran East Java. A quantitative approach is used in this research, with a sample size of 120 respondents determined using the Likert formula. The purposive sampling method was used to conduct the sampling technique. The Partial Least Squares (PLS) program was used to analyze the data. According to the findings, consumers' choices to buy iPhones are positively and significantly impacted by factors like brand image, product quality, and lifestyle.